Clinically significant personality traits in individuals at high risk of developing psychosis. (March 2018) - Sevilla-Llewellyn-Jones, Julia; Camino, Gustavo; Russo, Debra A.; Painter, Michelle; Montejo, Angel L.; Ochoa, Susana; Jones, Peter B.; Perez, Jesus
Abstract: It is still unclear to what extent personality may influence the development of psychosis. We aimed to explore significant personality traits in individuals at high-risk (HR) for psychosis. Personalities of forty HR individuals and a matched sample of 40 healthy volunteers (HVs) were evaluated with the Millon Multiaxial Inventory (MCMI-III). They were also assessed with the Positive and Negative Symptoms Scale (PANSS), Beck Depression and Anxiety Inventories (BDI-II and BAI), Global Assessment of Functioning (GAF) and Mini-International Neuropsychiatric Interview (MINI 6.0.0). Fisher's exact test was employed to compare frequency of traits. Mann-Whitney U test and logistic regression were used to establish relationships between traits and symptoms, and the effect of age, sex and symptoms on such traits. Most HR individuals (97.5%) had at least one significant trait; 75% had personality disorders, mainly depressive, borderline or schizotypal. Only histrionic and narcissistic traits were more prevalent in HVs. Negative symptoms were related to schizoid and paranoid traits. Depression was more severe with borderline traits. Most HR individuals (67.6%) had more than one DSM-IV Axis I diagnosis, mainly depressive/anxiety disorders. Transition rate was low (5%). Certain personality profiles may not be markers for conversions to psychosis but contribute to high morbidity in HR individuals. Highlights: Three in four individuals at high risk (HR) for psychosis had personality disorders. The most frequent traits in HR were depressive, borderline and masochistic. Borderline and paranoid traits were associated with depression in HR individuals.